Cambio climático: impuestos sobre el carbono, coste y eficiencia económica - García Fernández, Cristina (Nómadas. Critical Journal of Social and Juridical Science, 2012)
The purpose of this paper is the discussion, in a theoretic frame, of the most effective economic policies that could be employed to slow the impacts of climate change. Our aim is then to present most adequate economic instruments that are capable to slowing down the global warming rate of increase. We also make a comparison between those instruments in relation to their economic efficiency below different criteria. The case of a carbon tax has a special treatment in this paper due to the efficiency it shows in the market.
Keywords: carbon taxes; tradable emissions permits